The effect of conditioning stimulus intensity on conditioned pain modulation (CPM) hypoalgesia - Alexia Coulombe-Lévêque; Yannick Tousignant-Laflamme; Guillaume Léonard; Serge Marchand (Taylor & Francis Group, 2021)
Background: The magnitude and duration of conditioned pain modulation (CPM) likely depends on the nature and intensity of the conditioning stimulus (CS). Aims: The aim of this study was to measure the effect of CS intensity on the duration of CPM hypoalgesia. Methods: In this single-blind, nonrandomized, repeated measures study, we assessed CPM hypoalgesia in 20 healthy participants following cold pressor tests (CPT) at 7°C and 12°C. The test stimulus, a 60-s heat stimulation, was administered before the CPT and immediately after, and again at 5-min intervals until participants' pain scores returned to pre-CS levels. Two hypoalgesia thresholds were used to establish return to pre-CS level: within −10/100 of baseline and within −20/100 of baseline. Results: CPM hypoalgesia, when defined as a reduction in pain levels >10/100, did not last longer following the more intense 7°C CPT compared to the 12°C CPT (32 min vs. 20 min, respectively; P = 0.06); similar results were obtained when CPM hypoalgesia was defined as a reduction in pain levels of >20/100 (16 min following the 7°C CPT vs. 9 min following the 12°C CPT; P = 0.33). The duration of CPM hypoalgesia was significantly longer when the 10/100 threshold was used compared to the 20/100 threshold, regardless of CPT temperature (P = 0.008 for the 12°C CPT; P < 0.001 for the 7°C CPT). Conclusions: The more intense CS did not induce CPM hypoalgesia of longer duration compared to the less intense CS. The choice of threshold for what constitutes CPM hypoalgesia did have a significant effect on the results.